UAV orthophoto poster Seberang Takir, Terengganu - Abdullah, Alias; Ibrahim, Illyani; Ibrahim, Mansor; Hj. Mohd. Noor, Norzailawati; Harun, Nor Zalina; Abdul Latip, Nurul Syala; Abdullah, Ahmad Afiq Aiman; N Murtaza, Fatin Farhana (2020)
UAV Orthophoto of Seberang Takir, Terengganu with scale of 1:35000